Current View of the Clinical Management of Bruxism in Dentistry - Morales-Lastre, Cristian Camilo (2025)
Bruxism is a parafunctional activity involving repetitive movements of the masticatory muscles, often associated with stress, anxiety, and other psychosocial or physiological factors. This paper offers a comprehensive review of its clinical management, discussing diagnostic approaches and therapeutic strategies. Diagnostic methods include clinical examination, self-reported scales such as the CBA and PSS-14, electromyography, and polysomnography. Management requires an individualized, multidisciplinary approach. Occlusal splints remain the most widely used intervention for protecting dental structures. Botulinum toxin has shown efficacy in reducing muscle activity in severe cases, while physical therapies, acupuncture, and photobiomodulation (laser and LED) offer promising complementary options. LED therapy is emerging as a non-invasive alternative for pediatric patients. The findings suggest that early diagnosis and a personalized combination of conventional and alternative treatments can improve clinical outcomes. The integration of stress assessment tools and new technologies is essential for optimizing bruxism management in dental practice.